ZnO nanowire-decorated Al2O3hybrids for improving the thermal conductivity of polymer composites - Liu, Chao; Wu, Wei; Drummer, Dietmar; Shen, Wanting; Wang, Yi; Schneider, Kevin; Tomiak, Florian (Journal of Materials Chemistry C, 2020)
Thermal management is considered a crucial feature for the efficient integration of electronic devices; therefore, the requirement for polymer materials with excellent thermal conductivity is increasing. In this study, we designed and synthesized a novel hybrid filler composed of Al2O3spheres and needle-like zinc oxide nanowires, and then used it for the fabrication of thermally conductive polydimethylsiloxane (PDMS) composites. Furthermore, to sufficiently investigate the impact of the ZnO nanowire morphology on the thermal transfer ability of the composites, the aspect ratio of the nanowires was controlled by regulating the parameters of the hydrothermal reaction. The chemical structures and morphologies of the Al2O3-ZnO nanowire hybrids were confirmed by X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD) and scanning electron microscopy (SEM). The results indicated that the PDMS hybrid composites incorporated with 40 vol% hybrid filler decorated with high AR ZnO nanowires achieved the highest thermal conductivity of 1.185 W m-1K-1, which was about 6.77 times that of the pure PDMS matrix, and 46% higher than that of the Al2O3/PDMS composites. In addition, the hybrid filler also had positive influences on the mechanical property, thermal and dimensional stability of the PDMS composites due to its unique needle-like nanostructures. Our research demonstrated that the novel Al2O3-ZnO nanowire hybrid filler is an excellent candidate for the modification of thermal interface materials, which can be utilized in the thermal management of electronics.
CRIS-Team Scopus Importer:2020-05-15